2016
DOI: 10.4062/biomolther.2016.141
|View full text |Cite
|
Sign up to set email alerts
|

Lonchocarpine Increases Nrf2/ARE-Mediated Antioxidant Enzyme Expression by Modulating AMPK and MAPK Signaling in Brain Astrocytes

Abstract: Lonchocarpine is a phenylpropanoid compound isolated from Abrus precatorius that has anti-bacterial, anti-inflammatory, antiproliferative, and antiepileptic activities. In the present study, we investigated the antioxidant effects of lonchocarpine in brain glial cells and analyzed its molecular mechanisms. We found that lonchocarpine suppressed reactive oxygen species (ROS) production and cell death in hydrogen peroxide-treated primary astrocytes. In addition, lonchocarpine increased the expression of antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Nrf2 plays an important role in the up-regulation of antioxidant and detoxifying enzymes. Recent studies have shown that failure of the Nrf2 function promotes carcinogen-induced DNA damage and tumor formation [ 7 , 25 ]. Therefore, Nrf2 is an important molecular target for cancer prevention [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 plays an important role in the up-regulation of antioxidant and detoxifying enzymes. Recent studies have shown that failure of the Nrf2 function promotes carcinogen-induced DNA damage and tumor formation [ 7 , 25 ]. Therefore, Nrf2 is an important molecular target for cancer prevention [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 protein reduces oxidative stress. Nrf2/ARE signaling pathway reported for its neuroprotective effect on the basis of anti-oxidant and anti-inflammatory activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…The AMP-activated protein kinase (AMPK) and nuclear factor-E2-related factor-2 (Nrf2) pathways are involved in the regulation of inflammation and redox signaling [ 17 - 19 ]. Moreover, several papers have reported that AMPK contributes to the suppression of proinflammatory reactions via Nrf2 activation [ 20 - 22 ].…”
Section: Resultsmentioning
confidence: 99%